Nghiên cứu tổng hợp, đặc trưng vật liệu mao quản trung bình Al-MSU và xác định hoạt tính xúc tác trong phản ứng crackinh phân tử lớn. Phần I - Nghiên cứu tổng hợp, đặc trưng vật liệu mao quản trung bình Al-MSU - Đồng, Đỗ Xuân; Thanh Loan, Nguyễn Thị; Trìu, Nguyễn Ngọc; Tuấn, Vũ Anh; Hoài Nam, Lê Thị (Vietnam Journal of Chemistry, 2014)
Al-MSU mesoporous materials were successfully synthesized by hydrothermal treatment using water glass as a Si-sources. The obtained samples were characterized by different techniques such as x-ray diffraction (XRD), infrared resonance (IR) and transmission electron microscopy (TEM). The specific surface area (SBET) and mesopore volume, pore size distribution were determined by BET method. The results showed that the Al-MSU mesoporous materials were hexagonal p6mm structure.